A Chemical Study of Archaeometallurgical Ceramics from Southwestern Tanzania - Lyaya, Edwinus C. (Tanzania Journal of Engineering and Technology, 2023)
Archaeometallurgical ceramics, including furnaces, tuyères, and potteries, were required for successful pre-industrial iron smelting and refining. However, there are limited chemical studies on archaeometallurgical ceramics in Tanzania. This paper examined the nature of clay source in terms of refractoriness, determined whether there were multiple clay sources, and verified the refractoriness of the archaeometallurgical ceramics. An x-ray fluorescence (XRF) analytical technique and experimental re-firing of the archaeometallurgical ceramics were employed. The chemical data clustered in the mullite region on the Al2O3-SiO2-FeO ternary system indicate that iron smelters and refiners chose refractory clay sources for making archaeometallurgical ceramics. Small range and standard deviation suggest that the furnaces and tuyères were made from similar refractory clay source, while the relatively slight difference in range and standard deviation of the potteries indicate that they were made from another different clay source. The archaeometallurgical ceramics re-fired in the furnace lab did not bloat at 1300 oC, it verifies that they were indeed refractory. Keywords: furnaces, tuyères, potteries, smelting, refining, Sumbawanga, Mbozi